2016
DOI: 10.1186/s40644-016-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

CT-perfusion measurements in pancreatic carcinoma with different kinetic models: Is there a chance for tumour grading based on functional parameters?

Abstract: BackgroundTo evaluate the interchangeability of perfusion parameters obtained with help of models used for post-processing of perfusion-CT images in pancreatic adenocarcinoma and to determine the mean values and ranges of perfusion in different tumour gradings.MethodsPerfusion-CT imaging was performed prospectively in 48 consecutive patients with pancreatic adenocarcinoma. In 42 patients biopsy-proven tumor grading was available (4 × G1/24 × G2/14 × G3/6× unknown). Images were post-processed using a model base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…We used the deconvolution model for CT perfusion analysis since it can tolerate greater image noise than compartment models and was reported to be well suited for measuring lower levels of perfusion [ 33 ], as expected in PDAC. The deconvolution-based BF tumor values obtained in our current study were similar to previously reported deconvolution-based BF tumor values in PDAC [ 34 ], but considerably higher than previously reported BF tumor values based on the maximum-slope approach in PDAC [ 34 , 35 ]. This difference between BF tumor values obtained from the different models might be attributable to differences in the two mathematical calculation methods [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We used the deconvolution model for CT perfusion analysis since it can tolerate greater image noise than compartment models and was reported to be well suited for measuring lower levels of perfusion [ 33 ], as expected in PDAC. The deconvolution-based BF tumor values obtained in our current study were similar to previously reported deconvolution-based BF tumor values in PDAC [ 34 ], but considerably higher than previously reported BF tumor values based on the maximum-slope approach in PDAC [ 34 , 35 ]. This difference between BF tumor values obtained from the different models might be attributable to differences in the two mathematical calculation methods [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…The deconvolution-based BF tumor values obtained in our current study were similar to previously reported deconvolution-based BF tumor values in PDAC [ 34 ], but considerably higher than previously reported BF tumor values based on the maximum-slope approach in PDAC [ 34 , 35 ]. This difference between BF tumor values obtained from the different models might be attributable to differences in the two mathematical calculation methods [ 34 ]. Mean BV tumor and PEM tumor values were within the same range as those reported by Schneeweiß et al [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, Schneeweiss et al. (14) found no significant differences in perfusion parameters between different grades of pancreatic adenocarcinomas. Nevertheless, in the abovementioned study there were three groups of patients based on histological differentiation (G1–G3), while in the current study well- and moderately differentiated tumors were combined as one group because of rarity of well-differentiated tumors and due to similarity of their prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…This technique has been widely employed in the quantitative analysis of acute ischemic stroke in the brain [1][2][3]. As post-processing strategies and software have developed, the application of CTPI has expanded to more settings, including the assessment of hepatic and pancreatic lesions [4][5][6][7][8][9][10]. Specifically, liver CTPI has been shown to provide valuable information for the diagnosis and prognosis of liver diseases such as hepatic cirrhosis, hepatocellular carcinoma, and cancer metastasis to the liver [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%